2022
DOI: 10.3389/fmolb.2022.944774
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference (RNAi) applications to the management of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae): Its current trends and future prospects

Abstract: The fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is among the invasive insect pests that damages maize and sorghum, the high-priority crops in newly colonized agro-ecologies, including African contexts. Owing to the increasing infestation of the pest and the limitations of current conventional methods for its management, there is a call for discovering advanced pest management approaches. RNA interference (RNAi) is an emerging molecular tool showing flexible potential for the management of S. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…59 However, our study and other reports showed the feasibility and positive outcomes in S. frugiperda. 60 In addition, the Clustered Regularly Interspaced Short Palindromic Repeat/Cas9 (CRISPR/Cas9) system-mediated gene editing could effectively knockout the target genes. 40 In the…”
Section: Discussionmentioning
confidence: 99%
“…59 However, our study and other reports showed the feasibility and positive outcomes in S. frugiperda. 60 In addition, the Clustered Regularly Interspaced Short Palindromic Repeat/Cas9 (CRISPR/Cas9) system-mediated gene editing could effectively knockout the target genes. 40 In the…”
Section: Discussionmentioning
confidence: 99%
“…Examples of targets potentially underlying insecticide resistance in L. decemlineata and explored using dsRNA-based approaches are shown in Table 4 . Furthermore, while it is challenging to highlight these studies in the current work, it is relevant to underline that such an approach has seems promising to control a variety of insect pests, including the fall armyworm Spodoptera frugiperda [ 78 ], the whitefly Bemisia tabaci [ 79 ], and the emerald ash borer Agrilus planipennis [ 80 ].…”
Section: Rnai and Insecticide Resistancementioning
confidence: 99%
“…Examples of targets potentially underlying insecticide resistance in L. decemlineata and explored using dsRNA-based approaches are shown in Table 4. Furthermore, while it is challenging to highlight these studies in the current work, it is relevant to underline that such an approach has seems promising to control a variety of insect pests, including the fall armyworm Spodoptera frugiperda [78], the whitefly Bemisia tabaci [79], and the emerald ash borer Agrilus planipennis [80]. ABCH278B, ABCH278C, ABCG1041A Imidacloprid dsRNA feeding in adults [51] CncC, CYP6BJa/b, CYP6BJ1v1, CYP9Z25, CYP9Z29 Imidacloprid dsRNA feeding in adults [41] CP18.7, CYP9E2, Glutathione synthetase Imidacloprid dsRNA feeding in larvae [77] While several advantages are associated with strategies that rely on RNAi-based approaches to overcome insecticide resistance in insect pests, multiple challenges are, nevertheless, linked with their use in field-based applications and have been reviewed elsewhere [63,[81][82][83].…”
Section: Rnai and Insecticide Resistancementioning
confidence: 99%
“…Thus, there is an urgent need for the development of new control strategies of FAW. Recently, RNA interference (RNAi) triggered by double-stranded RNA (dsRNA) has evolved as a promising strategy for the management of insect pests including FAW. …”
Section: Introductionmentioning
confidence: 99%